Normal Echocardiographic Reference Values of the Right Ventricular to Left Ventricular Endsystolic Diameter Ratio and the Left Ventricular Endsystolic Eccentricity Index in Healthy Children and in Children With Pulmonary Hypertension - Schweintzger, Sabrina; Kurath-Koller, Stefan; Burmas, Ante; Grangl, Gernot; Fandl, Andrea; Noessler, Nathalie; Avian, Alexander; Gamillscheg, Andreas; Chouvarine, Philippe; Hansmann, Georg; Koestenberger, Martin (Frontiers in Cardiovascular Medicine, 2022)
Background: An accurate assessment of the right ventricle and left ventricle and their interaction is important in pediatric pulmonary hypertension (PH). Our objective was to provide normal reference values for the right ventricular to left ventricular endsystolic (RV/LVes) ratio and the LV endsystolic eccentricity index (LVes EI) in healthy children and in children with PH. Methods: We conducted an echocardiographic study in 769 healthy children (median age: 3.36 years; range: 1 day to 18 years) and validated abnormal values in 44 children with PH (median age: 2.1 years; range: 0.1 months to 17.7 years). We determined the effects of gender, age, body length, body weight, and body surface area on RV/LVes ratio and LVes EI values. Results: Both, the RV/LVes ratio and the LVes EI were highly age-dependent: i) neonates RV/LVes ratio [median 0.83 (range 0.53–1.37)], LVes EI [1.21 (0.92–1.45)]; ii) 12-24 months old: RV/LVes ratio: [0.55 (0.35–0.80)], LVes EI: [1.0 (0.88–1.13)]; iii) 18th year of life RV/LVes ratio: [0.53 (0.32-0.74)], LVes EI: [1.0 (0.97–1.07)]. Children (>1 year) and adolescents with PH had a significantly higher RV/LVes ratio (no PH: median 0.55, IQR 0.49–0.60; PH: 1.02, 0.87–1.26; p<0.001) and higher LVes EI values (no PH: 1.00, 0.98–1.00; PH: 1.53, 1.26–1.71; p<0.001) compared to those without PH. To predict the presence of PH in children older than 1 year, we found the following best cutoff values: RV/LVes ratio >0.67 (sensitivity: 1.00, specificity: 0.95) and LVes EI >1.06 (sensitivity: 1.00, specificity: 0.97). Conclusions: We provide normal echocardiographic reference values of the RV/LVes ratio and LVes EI in healthy children, as well as statistically determined cutoffs for the increased values in children with PH.